Arginine vasopressin improves cerebral perfusion following controlled haemorrhage in adult ewes. (19th July 2019) - Berry, Mary J.; Darby, Jack R. T.; O'Byrne, David M.; Dyson, Rebecca M.; Sixtus, Ryan; Holman, Stacey L.; Abelentseva, Alexandra; Bowler, Paul; Stanbridge, Kate; Morrison, Janna L.
Abstract : Key points: Traumatic haemorrhagic shock carries significant morbidity and mortality related to the severity and duration of tissue hypoperfusion, much of which occurs in the pre‐hospital environment where therapy must be easy to use and would augment, not replace, local haemorrhage control measures. Vasopressor therapy use in haemorrhagic shock remains controversial. Potential benefits from improved blood pressure and tissue perfusion need to be weighed against possible harm from increased blood loss if haemorrhage is uncontrolled. We demonstrate that 20 IU I.M. vasopressin produces a progressive, sustained and clinically significant increase in blood pressure and carotid blood flow compared to 1 mg I.M. adrenaline or placebo in an animal model of controlled haemorrhagic shock. I.M. vasopressin may play a role in the early management of haemorrhagic shock by improving cerebral perfusion and haemodynamic stability; however, further studies are required to establish the potential benefit against the risk of exacerbating haemorrhage, if it is uncontrolled. Abstract: Haemorrhagic shock causes significant morbidity and mortality. Novel pre‐hospital therapy to improve haemodynamic stability and cerebral perfusion may improve outcomes but remains controversial. In an ovine model of controlled haemorrhagic shock, the effects of early intramuscular arginine vasopressin (AVP), adrenaline or placebo on haemodynamic stability and cerebral perfusion were compared. Carotid pressure and flow catheters were placed in healthy, anaesthetized adult ewes. Frontal cortex cerebral oxygenation was measured using near infrared spectroscopy. Controlled, rapid, haemorrhage (∼30% estimated blood volume) was induced. Five minutes post‐bleed a 1 ml intramuscular dose of 0.9% saline, adrenaline 1 mg or AVP 20 IU was administered. Carotid blood pressure and flow improved significantly in the AVP group over the first 30 min post‐intervention. To emulate standard trauma care, 1 L of 0.9% saline was infused 30 min post‐bleed followed by re‐transfusion of the sheep's own blood at 60 min post‐bleed. Carotid blood pressure and flow in the AVP group remained significantly higher post‐crystalloid infusion, but this difference was lost post‐blood transfusion. Data were analysed by two‐way ANOVA with time, group as the main factors. When compared to saline or adrenaline, a single dose of intramuscular AVP resulted in a progressive and sustained increase in carotid artery blood pressure and flow with commensurate increase in cerebral oxygenation. Intramuscular AVP has potential as an emergency pre‐hospital therapy following exsanguinating haemorrhage; however, further studies are required to investigate whether the benefit of improved perfusion pressure outweighs the risks of exacerbating ongoing bleeding. Key points: Traumatic haemorrhagic shock carries significant morbidity and mortality related to the severity and duration of tissue hypoperfusion, much of which occurs in the pre‐hospital environment where therapy must be easy to use and would augment, not replace, local haemorrhage control measures. Vasopressor therapy use in haemorrhagic shock remains controversial. Potential benefits from improved blood pressure and tissue perfusion need to be weighed against possible harm from increased blood loss if haemorrhage is uncontrolled. We demonstrate that 20 IU I.M. vasopressin produces a progressive, sustained and clinically significant increase in blood pressure and carotid blood flow compared to 1 mg I.M. adrenaline or placebo in an animal model of controlled haemorrhagic shock. I.M. vasopressin may play a role in the early management of haemorrhagic shock by improving cerebral perfusion and haemodynamic stability; however, further studies are required to establish the potential benefit against the risk of exacerbating haemorrhage, if it is uncontrolled.